Expandable Battery Pad
The expandable battery pad with polyurethane foam and intumescent material addresses thermal runaway in lithium-ion batteries, enhancing safety without compromising energy density.
Patent Information
- Application Number
- JP2021573240
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-06-10
- Filing Date
- 2020-06-04
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-06-04
AI Technical Summary
Large lithium-ion batteries face safety issues due to thermal runaway, which can lead to cascading fires, and existing safety measures compromise energy density or electrochemistry performance.
An expandable battery pad comprising polyurethane foam with an intumescent material containing an acid source, carbon source, and blowing agent, providing thermal insulation and flame retardancy.
The expandable battery pad effectively mitigates thermal runaway propagation while maintaining high energy density and electrochemical performance.
Smart Images

Figure 0007609812000001 
Figure 0007609812000002 
Figure 0007609812000003
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO TECHNICALLY RELATED APPLICATIONS This application claims the benefit of U.S. Provisional Patent Application No. 62 / 859,230, filed June 10, 2019. The related applications are incorporated herein by reference in their entireties.
[0002] This application relates to expandable battery pads, battery assemblies, and more particularly to battery assemblies including expandable battery pads that can be used with lithium ion batteries. [Background technology]
[0003]
[0002] Demand for electrochemical energy storage devices such as lithium-ion batteries is increasing due to the growth of applications such as electric vehicles and grid energy storage systems, as well as other multi-cell battery applications such as electric bicycles, uninterruptible power battery systems, and lead-acid replacement batteries. In large format applications such as grid storage and electric vehicles, multiple cells connected in series and parallel arrays are often used. Such cells may be large (e.g., having at least 10 ampere hours (Ah)). An ongoing issue with large cells is safety, since the energy released in a cell going into thermal runaway is proportional to the amount of electrolyte and active material present in the cell and accessible during thermal runaway. In other words, because large cells contain a large amount of electrolyte and active material, thermal runaway can result in more intense fires. In addition, when a large cell goes into thermal runaway mode, the heat generated by the cell can induce thermal runaway propagation reactions in adjacent cells, causing a cascade effect that ignites the entire pack, causing destruction of the pack and surrounding equipment, as well as a potentially dangerous condition for the user.
[0004]
[0003] Attempts to reduce the flammability of such batteries have been considered, but they are not without drawbacks. For example, modifying the electrolyte by adding flame retardant additives or by using an essentially non-flammable electrolyte has been considered, but these attempts may adversely affect the electrochemical performance of the lithium-ion battery cell. Other approaches to prevent cascading thermal runaway include increasing the amount of insulation between cells or clusters of cells to reduce the amount of heat transfer during a thermal event. These approaches may limit the upper limit of the achievable energy density. Summary of the Invention [Problem to be solved by the invention]
[0005]
[0004] As the demand for high energy density batteries increases, the risk of flame generation and propagation increases.Therefore, there is a need in the art for batteries that can meet or exceed current flame safety standards.It would be an additional advantage if batteries could function at the desired higher energy. [Means for solving the problem]
[0006]
[0005] An expandable battery pad for lithium ion batteries is disclosed, the expandable battery pad comprising: a polyurethane foam having a compressive force deflection of 5 to 1,035 kilopascals at 25% deflection determined in accordance with ASTM D3574-17; and an expandable material comprising an acid source, a carbon source, and a blowing agent, wherein the expandable battery pad has a UL-V0 rating at a thickness of 1 millimeter.
[0007]
[0006] Also disclosed is a method of making an expandable battery pad, comprising the steps of: coating a foam composition comprising a reactive mixture onto a release liner; and curing the reactive mixture to form the polyurethane foam; wherein the foam composition comprises the expandable material or the method further comprises the step of depositing the expandable material onto at least one surface of the polyurethane foam to form the expandable battery pad.
[0008]
[0007] Further disclosed is a method of making an expandable battery pad, comprising depositing the expandable material onto the polyurethane foam.
[0009]
[0008] Also disclosed in the specification is a battery assembly comprising at least two battery cells and an expandable battery pad positioned between the at least two battery cells or along a surface adjacent to the battery assembly; the expandable battery pad comprising polyurethane foam and a layer of expandable material on the polyurethane foam.
[0010]
[0009] Further disclosed is a battery assembly and a battery including the expandable battery pad.
[0011]
[0010] The above and other features are illustrated by the following figures, detailed description, and claims.
[0012]
[0011] The following figures are exemplary embodiments and are provided to illustrate the present disclosure. The figures illustrating the examples are not intended to limit devices manufactured according to the present disclosure to the materials, conditions, or process parameters described herein. [Brief description of the drawings]
[0013] [Figure 1]
[0012] FIG. 1 illustrates an embodiment of a battery assembly including an expandable battery pad disposed between two battery cells. [Diagram 2] FIG. 1 shows another embodiment of a battery assembly including an expandable battery pad disposed between two battery cells. [Diagram 3]
[0014] FIG. 1 illustrates an embodiment of a battery assembly including an expandable battery pad disposed between an array of battery cells. [Figure 4]
[0015] FIG. 1 illustrates an embodiment of a battery assembly including expandable battery pads disposed between battery cells in an array of battery cells. [Diagram 5]
[0016] FIG. 1 illustrates an embodiment of a battery including an array of battery cells. [Figure 6]
[0017] FIG. 1 illustrates one embodiment of forming an expandable material. [Figure 7]
[0018] 1 is a photograph of the expandable battery pad of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014]
[0019] The problem of thermal runaway in batteries containing multiple cells is a difficult one because cells adjacent to a cell experiencing thermal runaway can absorb enough energy from the event to trigger their own cells to also go into thermal runaway. This propagation of the initiation of a thermal runaway event can create a chain reaction in which the storage device goes into a series of cascading thermal runaways as cells ignite adjacent cells.
[0015]
[0020] To prevent such cascading thermal runaway events from occurring, a battery assembly was developed that includes at least two battery cells and an expandable battery pad. The expandable battery pad includes a polyurethane foam and an expandable material. The expandable material includes an acid source, a carbon source, and a blowing agent. The expandable material can be dispersed in the polyurethane foam or can be present on at least one surface of the polyurethane foam. The fact that the expandable battery pad could be successfully used in a battery pack was surprising because the inherent expansion of the expandable material during a char event was thought to be too significant for use in a battery pack. Furthermore, it was surprising that the expandable material could be successfully coated onto the expandable battery pad while maintaining the desired foam properties of the polyurethane, because the addition of a coating was expected to adversely affect properties such as compression force deflection or compression set of the polyurethane foam.
[0016]
[0021] As described above, the battery assembly includes at least two battery cells and an expandable battery pad, which may be disposed between the at least two battery cells or along a surface adjacent to the battery assembly. The battery cells may be lithium ion battery cells. The particular shapes of the cells and the expandable battery pad may vary widely depending on the desired size or shape of the cells, the size or placement of the case or other structure that will house the cells, the manufacturing cost, the ease of manufacturing various shapes, and similar considerations, although effectiveness in heat shielding may be a primary consideration. For example, the battery cells may have a perimeter that is circular, square, rectangular, oval, trapezoidal, or other shape, and the expandable battery pad may have a perimeter that is correspondingly circular, square, rectangular, oval, trapezoidal, or other shape. Alternatively, the shape of the perimeter of at least one of the battery cells may be a different perimeter than the perimeter of the pad. For example, a cell having a circular perimeter may be used with an expandable battery pad having a rectangular perimeter.
[0017]
[0022] 1-4 show an exemplary embodiment of a battery assembly. FIG. 1 shows a battery assembly 10 in which an inflatable battery pad 4 is disposed between a first battery cell 2 and a second battery cell 6. The inset of FIG. 1 shows that the inflatable battery pad 4 can include a polyurethane layer 204 in direct physical contact with the inflatable layer 104. FIG. 1 further shows that the inflatable battery pad 4 can be approximately the same size as the battery cells, particularly across the width and height of the battery cells. For example, as shown in FIG. 1, the width in the x-direction and the height in the y-direction can be the same. In other aspects, the width and height of the inflatable battery pad 4 can be within ±0.2%, or ±0.5%, or ±1%, or ±2%, or ±3%, or ±5%, or ±10% of the width and height of at least one, and preferably both, of the battery cells. When different sized battery cells are used, the width and height of the expandable battery pad may be the same as one of the battery cells, or may be within ±0.2%, ±0.5%, or ±1%, or ±2%, or ±3%, or ±5%, or ±10% of the width and height of one of the battery cells. In one embodiment, particularly for assemblies having a circular or other non-square shape, the perimeter (measured as the length) may be within ±0.2%, ±0.5%, or ±1%, or ±2%, or ±3%, or ±5%, or ±10% of the perimeter of at least one, and preferably both, of the battery cells.
[0018]
[0023] However, the variation in size of the expandable battery pad is not limited to these amounts. At least one of the width in the x direction and the height in the y direction can be varied. FIG. 2 shows a battery assembly 20 in which the expandable battery pad 4 can be smaller than the respective battery cells in at least one direction. As shown in FIG. 2, the width of the expandable battery pad 4 in the x direction is the same as the width of the battery cells 2, 6, but the height of the expandable battery pad 4 in the y direction is significantly less than the height of the battery cells 2, 6. In other embodiments, both the width and the height can be different from the battery cells 2, 6.
[0019]
[0024] It is also possible that the inflatable battery pad varies only along a portion of the perimeter of one or more battery cells. In this embodiment, the perimeter of the battery pad is not uniform (does not share a border) with all edges of at least one battery cell. For example, as shown in FIG. 3, a battery assembly 40 includes battery cells 2, 6 having the same sized perimeter. An inflatable battery pad 4 is disposed between the battery cells 2, 6. At the edges 2b, 6b of the cells 2, 6, the battery pad 4 is uniform (shares a border) with the edges 2b, 6b. However, a portion 8 of the inflatable battery pad 4 is cut away to leave a notch in the pad. The notch can be used, for example, to easily insert another component of the battery. At the edges 2a, 6a of the cells 2, 6, the edge 10 of the battery pad 4 extends beyond the edges 2a, 6a to form a tab or flap. This additional material can be used, for example, for additional coverage of the battery cell or to fill a space between the battery cell and another structure within the battery, such as the casing of the battery. Any one or combination of the above features can be present in the battery assembly.
[0020]
[0025] FIG. 4 shows a battery assembly 40 including an array of battery cells arranged in a stack. The battery assembly 40 may include a plurality of battery cells 2, 6 with a plurality of expandable battery pads 4 disposed between each battery cell. The battery assembly may include a stack of 2-100 or 10-50 battery cells, with the expandable battery pads 4 disposed between at least two battery cells. Preferably, the expandable battery pads 4 are disposed between each battery cell in the stack.
[0021]
[0026] FIG. 5 shows a battery including a battery assembly 40. The battery can include a top casing 100 and a bottom casing 150. The top casing 100 and the bottom casing 150 can form a housing that surrounds the battery assembly. The top casing 100 and the bottom casing 150 can form a tight seal that can be reinforced by the presence of a gasket 110. It should be noted that the housing is not limited to the illustration and various other configurations are contemplated. The foam layer 120 can be disposed on one or more sides of the battery assembly 40. The foam layer 120 can be an expandable battery pad as disclosed herein. The foam layer 120 can be disposed along a surface proximate to the battery assembly 40. The major axis of the foam layer 120 can be perpendicular to the major axes of the battery cells 2 and 6. For example, the plane of the foam layer 120 can be in the xz plane and the plane of the battery cells 2, 6 can be in the xy plane. The battery can include a thermal management assembly including, for example, a thermal interface layer 130 and a cold plate 140 .
[0022]
[0027] The intumescent material includes an acid source, a blowing agent, and a carbon source. Each of these components can be present as a separate layer or as a mixture, preferably as an intimate mixture. For example, the intumescent material can include a polyphosphoric acid source, a blowing agent, and a pentaerythritol carbon source. Without being bound by theory, it is believed that the intumescent material can reduce the spread of a flame using two energy absorption mechanisms including forming a char and then expanding the char. For example, as the temperature reaches a value of, for example, 200-280°C, the acidic species (e.g., polyphosphoric acid) can react with the carbon source (e.g., pentaerythritol) to form a char. As the temperature increases to, for example, 280-350°C, the blowing agent can decompose to produce gaseous products that expand the char.
[0023]
[0028] The acid source can include at least one of organic or inorganic phosphorus compounds or organic or inorganic sulfates (e.g., ammonium sulfate) or other compounds. The organic or inorganic phosphorus compounds can include at least one of organic phosphates or organic phosphonates (e.g., tris(2,3-dibromopropyl)phosphate, tris(2-chloroethyl)phosphate, tris(2,3-dichloropropyl)phosphate, tris(1-chloro-3-bromoisopropyl)phosphate, bis(1-chloro-3-bromoisopropyl)-1-chloro-3-bromoisopropylphosphonate, polyaminotriazine phosphate, melamine phosphate, triphenyl phosphate, or guanylurea phosphate); organic phosphate esters (e.g., trimethyl phosphite or triphenyl phosphite); phosphazenes (e.g., hexaphenoxycyclotriphosphazene), phosphorus-containing inorganic compounds (e.g., phosphoric acid, phosphorous acid, phosphite, urea phosphate, or ammonium phosphate (e.g., ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, or ammonium polyphosphate)).
[0024]
[0029] The blowing agent can include an agent that decomposes (e.g., into smaller compounds such as ammonia or carbon dioxide) at temperatures above 120° C., e.g., 120-200° C. or 130-200° C. The blowing agent can include at least one of dicyandiamide, azodicarbonamide, melamine, guanidine, glycine, urea (e.g., urea-formaldehyde resin or methylolated guanylurea phosphate), or halogenated organic materials (e.g., chlorinated paraffins).
[0025]
[0030] It should be noted that the expandable material can include a carbon source, where the polyurethane foam itself can function as the carbon source. The carbon source can include at least one of dextrin, phenol-formaldehyde resin, pentaerythritol (e.g., its dimer or trimer), clay, or a polymer (e.g., polyamide 6, amino-poly(imidazoline-amide), or polyurethane). The amino-poly(imidazoline-amide) can include repeating amide bonds and imidazoline groups.
[0026]
[0031] The intumescent material can optionally include a synergistic compound to further improve the flame retardancy of the intumescent material. The synergistic compound can include at least one of a boron compound (e.g., zinc borate, boron phosphate, or boron oxide), a silicon compound, an aluminosilicate, a metal oxide (e.g., magnesium oxide, iron oxide, or aluminum oxide hydrate (boehmite)), or a metal salt (e.g., an alkali metal salt or alkaline earth metal salt of an organic sulfonic acid, or an alkaline earth metal carbonate). A preferred synergistic combination includes a phosphorus-containing compound having at least one of the above.
[0027]
[0032] The expandable material may further include a binder, if desired. The binder may include at least one of an epoxy, a polysulfide, a polysiloxane, and a polysilarylene. The binder may be present in the expandable material in an amount of 50% by weight or less, or 5-50% by weight, or 35-45% by weight, based on the total weight of the expandable material. The binder may be present in the expandable material in an amount of 5-95% by weight, or 40-60% by weight, based on the total weight of the expandable material.
[0028]
[0033] The expandable battery pad comprises a polyurethane foam. Generally, the polyurethane foam is formed from a reactive composition comprising an organic isocyanate component, a surfactant, and a catalyst that reacts with an active hydrogen-containing component. The organic isocyanate component used in the production of the polyurethane foam has the general formula: Q(NCO) i where i is an integer having an average value of 2 or greater, and Q is an organic radical having a valence of i. Q can be a substituted or unsubstituted group (e.g., an alkane or aromatic group of appropriate valence). Q has the formula Q 1 -ZQ 1 (In the formula, Q 1 is an alkylene or arylene group, and Z is -O-, -OQ 1 -S-, -CO-, -S-, -SQ 1 Q may represent a polyurethane radical having a valence of i.
[0029]
[0034] Examples of suitable isocyanates include hexamethylene diisocyanate, 1,8-diisocyanato-p-methane, xylyl diisocyanate, diisocyanatocyclohexane, phenylene diisocyanate, 2,4-tolylene diisocyanate, tolylene diisocyanates including 2,6-tolylene diisocyanate, and crude tolylene diisocyanate, bis(4-isocyanatophenyl)methane, chlorophenylene diisocyanate, diphenylmethane-4,4'-diisocyanate (also known as 4,4'-diphenylmethane diisocyanate or MDI) and its adducts, naphthalene-1,5-diisocyanate, triphenylmethane-4,4',4"-triisocyanate, isopropylbenzene-α-4-diisocyanate, or polymeric isocyanates such as polymethylene polyphenylisocyanate.
[0030]
[0035] The active hydrogen-containing component may comprise a polyol (e.g., at least one of a polyether polyol or a polyester polyol). Suitable polyester polyols include polycondensation products of polyols with dicarboxylic acids or their ester-forming derivatives (e.g., anhydrides, esters and halides), polylactone polyols obtained by ring-opening polymerization of lactones in the presence of polyols, polycarbonate polyols obtained by reaction of carbonate diesters with polyols, or castor oil polyols. Suitable dicarboxylic acids and dicarboxylic acid derivatives useful for producing polycondensation polyester polyols are aliphatic or cycloaliphatic dicarboxylic acids, such as glutaric acid, adipic acid, sebacic acid, fumaric acid or maleic acid; dimer acids; aromatic dicarboxylic acids, such as phthalic acid, isophthalic acid or terephthalic acid; tribasic or higher functional polycarboxylic acids, such as pyromellitic acid; and anhydrides or secondary alkyl esters, such as maleic anhydride, phthalic anhydride or dimethyl terephthalate.
[0031]
[0036] Polyols can have hydroxyl numbers that vary over a wide range. In general, the hydroxyl number of polyols, including other crosslinking additives, if used, can be from 28 to 1,000, or from 100 to 800. The hydroxyl number is defined as the number of milligrams of potassium hydroxide required for complete neutralization of the hydrolysis product of a fully acetylated derivative prepared from one gram of polyol or a mixture of polyols with or without other crosslinking additives.
[0032]
[0037] Methods for producing foams are generally known. Foams can be mechanically foamed, physically or chemically sprayed, or both. Polyurethane foams can be made by casting a mechanically foamed composition. In particular, reactive precursors of polyurethane can be mixed, mechanically foamed, then cast to form layers, and cured.
[0033]
[0038] Physical blowing agents can be used alone or in mixtures with each other or with one or more chemical blowing agents. Physical blowing agents can be selected from a wide range of materials including hydrocarbons, ethers, esters and partially halogenated hydrocarbons, ethers and esters, etc. Typical physical blowing agents have boiling points of -50 to 100°C, or -50 to 50°C. Exemplary physical blowing agents include CFC's (chlorofluorocarbons) (e.g., 1,1-dichloro-1-fluoroethane, 1,1-dichloro-2,2,2-trifluoroethane, monochlorodifluoromethane, or 1-chloro-1,1-difluoroethane); FC's (fluorocarbons) (e.g., 1,1,1,3,3,3-hexafluoropropane, 2,2,4,4-tetrafluorobutane, 1,1,1,3,3,3-hexafluoro-2-methylpropane, 1,1,1,3,3-pentafluoropropane, 1,1,1,2,2-pentafluoropropane, 1,1,1,2,3-pentafluoropropane, 1,1,2,2,3-pentafluoropropane, 1,1,2,2,3-pentafluoropropane, pentafluoropropane, 1,1,1,3,3,4-hexafluorobutane, 1,1,1,3,3-pentafluorobutane, 1,1,1,4,4,4-hexafluorobutane, 1,1,1,4,4-pentafluorobutane, 1,1,2,2,3,3-hexafluoropropane, 1,1,1,2,3,3-hexafluoropropane, 1,1-difluoroethane, 1,1,1,2-tetrafluoroethane or pentafluoroethane; FE's (fluoroethers) (e.g., methyl-1,1,1-trifluoroethyl ether, difluoromethyl-1,1,1-trifluoroethyl ether); or hydrocarbons (e.g., n-pentane, isopentane, cyclopentane); and the like. The physical blowing agents can include at least one of carbon dioxide, ethane, propane, n-butane, isobutane, pentane, hexane, butadiene, acetone, methylene chloride, any chlorofluorocarbon, hydrochlorofluorocarbon, or hydrofluorocarbon. As with the chemical blowing agents, the physical blowing agents can be used in an amount sufficient to impart the desired bulk density to the resulting foam.Typically, the physical blowing agent is used in an amount of 5 to 50 weight percent or 10 to 30 weight percent based on the total weight of the reactive composition.
[0034]
[0039] When a chemical blowing agent is used, it may be water, an azo compound (e.g., azoisobutyronitrile, azodicarbonamide (i.e., azo-bis-formamide), or barium azodicarboxylate); a substituted hydrazine (e.g., diphenylsulfone-3,3'-disulfohydrazide, 4,4'-hydroxy-bis(benzenesulfohydrazide), trihydrazinotriazine, or an aryl-bis(sulfohydrazide)); a semicarbazide (e.g., p-tolylenesulfonylsulfate, The blowing agent may include at least one of: micarbazide, or 4,4'-hydroxy-bis(benzenesulfonylsemicarbazide); triazoles (e.g., 5-morpholinyl-1,2,3,4-thiatriazole); N-nitroso compounds (e.g., N,N'-dinitrosopentamethylenetetramine or N,N-dimethyl-N,N'-dinitrosophthalamide); benzoxazines (e.g., isatoic anhydride); or mixtures (e.g., sodium carbonate / citric acid mixtures). The chemical blowing agent may include water. The blowing agent may include at least one of ammonium salts, phosphates, polyphosphates, borates, polyborates, sulfates, urea, urea-formaldehyde resins, dicyandiamide, or melamine.
[0035]
[0040] The amount of the above-mentioned chemical foaming agents varies depending on the agent and the desired foam density, and can be easily determined by those skilled in the art. Generally, these chemical foaming agents are used in an amount of 0.1-10% by weight based on the total weight of the reactive composition. The decomposition products formed during the decomposition process may be physiologically safe, and they may not have a significant adverse effect on the thermal stability or mechanical properties of the foamed polyurethane sheet.
[0036]
[0041] Many catalysts can be used to catalyze the reaction between the isocyanate component and the active hydrogen-containing component, including organic and inorganic acid salts or organometallic derivatives of bismuth, lead, tin, iron, antimony, uranium, cadmium, cobalt, thorium, aluminum, mercury, zinc, nickel, cerium, molybdenum, vanadium, copper, manganese, or zirconium, as well as phosphines or tertiary organic amines. Examples of such catalysts are dibutyltin dilaurate, dibutyltin diacetate, stannous octoate, lead octoate, cobalt naphthenate, triethylamine, triethylenediamine, N,N,N',N'-tetramethylethylenediamine, 1,1,3,3-tetramethylguanidine, N,N,N'N'-tetramethyl-1,3-butanediamine, N,N'-dimethylethanolamine, N,N-diethylethanolamine, 1,3,5-tris(N,N-dimethylaminopropyl)-s-hexahydrotriazine, o- and p-(dimethylaminomethyl)phenol, 2,4,6-tris(dimethylaminomethyl)phenol, N,N-dimethylcyclohexylamine, pentamethyldiethylenetriamine, 1,4-diazobicyclo[2.2.2]octane, N-hydroxylalkyl quaternary ammonium carboxylates and tetramethylammonium formate, tetramethylammonium acetate or tetramethylammonium 2-ethylhexanoate.
[0037]
[0042] The catalyst may include metal acetylacetonates based on metals such as aluminum, barium, cadmium, calcium, cerium (III), chromium (III), cobalt (II), copper (II), indium, iron (II), lanthanum, lead (II), manganese (II), manganese (II), manganese (III), neodymium, nickel (II), palladium (II), potassium, samarium, sodium, terbium, titanium, vanadium, yttrium, zinc, or zirconium. The catalyst may include bis(2,4-pentanedionato)nickel(II) (also known as nickel acetylacetonate or nickel diacetylacetonate) or a derivative thereof, such as nickel diacetonitrile diacetylacetonate, nickel diphenylnitrile diacetylacetonate, or nickel bis(triphenylphosphine) diacetylacetylacetonate. The catalyst may include iron acetylacetonate (FeAA).
[0038]
[0043] The amount of catalyst present in the reactive composition can be 0.03 to 3 weight percent, based on the total weight of the active hydrogen-containing components. The reactive composition can include acetylacetone (2,4-pentanedione), which can provide thermal latency, allowing time for required mixing, casting, and other procedures, and can help avoid deleterious premature curing during low temperature processing. Generally, the weight ratio of catalyst to acetylacetone can be 3:1 to 1:1.
[0039]
[0044] The reactive composition may include a surfactant capable of stabilizing the reactive composition prior to curing. The surfactant may include an organosilicone surfactant. The organosilicone may include a surfactant having a SiO2 (silicate) unit and a (CH3)3SiO 0.5The copolymer may comprise or consist essentially of (trimethylsiloxy) units in a molar ratio of silicate to trimethylsiloxy units of 0.8:1 to 2.2:1 or 1:1 to 2.0:1. The organosilicone may comprise a partially crosslinked siloxane-polyoxyalkylene block copolymer, in which the siloxane block and the polyoxyalkylene block are bonded to carbon by silicon or to carbon by oxygen by silicon. The surfactant may be present in an amount of 0.5 to 10 weight percent or 1 to 6 weight percent, based on the total weight of the active hydrogen component.
[0040]
[0045] Other optional additives can be added to the reactive composition. For example, additives can include fillers (e.g., alumina trihydrate, silica, talc, calcium carbonate, or clay), dyes, pigments (e.g., titanium dioxide or iron oxide), antioxidants, antiozonants, UV stabilizers, conductive fillers, or conductive polymers.
[0041]
[0046] Polyurethane foams can be produced by mechanically mixing a reactive composition (e.g., including an isocyanate component, an active hydrogen-containing component, a foam-stabilizing surfactant, a catalyst, and other optional additives) with a foam-forming gas. As shown in FIG. 6, the foam mixture 10 can be continuously fed from unit 12, e.g., via conduit 14, onto release liner 16. The release liner can be regenerated from feed roll 18, pulled to the right by rolls 20 and 22 to pass through various stations in the system, and can be rewound onto take-up roll 24. As release liner 16 is moved to the right with foam mixture 10 deposited thereon, foam mixture 10 is spread into a layer of the desired thickness by doctor blade 26 or other suitable application device. Doctor blade 26 spreads foam mixture 10 to the desired thickness, e.g., 0.1 to 15 millimeters, to form a gauged layer.
[0042]
[0047] The gauged layer of foam mixture can then be delivered to one or more heating zones, for example a first heating zone including infrared heaters 46, or a second heating zone including heated platens 28 and 30. Platens 28 and 30 can be parallel and have an equidistant spacing between them along their length, or they can diverge from inlet 32 to outlet 34. If the top layer of foam directly opposite heated platen 30 is not covered with another layer of release liner, the spacing between platens 28 and 30 can exceed the worked thickness of the layers of foam material and release support 16, thereby preventing the unexposed top surface of the foam from contacting heated platen 30. The temperature of each heating zone can be independently between 90 and 250°C. After the heating zones, the formed polyurethane layer is sent to a cooling zone where it can be cooled by any suitable cooling device, such as fan 38. The formed polyurethane layer can then be taken up onto roll 40, optionally after removing release liner 16.
[0043]
[0048] The expandable battery pad includes a polyurethane foam and an expandable material. The expandable material can be dispersed in the polyurethane foam or can be present on at least one surface of the polyurethane foam. When the expandable material is present in the polyurethane foam, the expandable material can be present in a reactive composition including a polyurethane precursor composition prior to forming the polyurethane foam, or the expandable material can be added to the foam post-processing, for example, by saturating the polyurethane foam with a liquid composition including the expandable material. In this embodiment, the expandable material can permeate the polyurethane material itself.
[0044]
[0049] Alternatively, or in addition, the liquid composition including the expandable material can penetrate the pores of the polyurethane material and coat or fill at least a portion of the surfaces of the pores, conveniently referred to herein as the "inner surfaces." In this aspect, the coating or filling is done so as not to substantially adversely affect the desired properties of the foam, such as the compression deflection or compression set of the foam.
[0045]
[0050] In another embodiment in which the expandable material is present on at least one surface of the polyurethane foam, the expandable material is present on at least one outer surface of the polyurethane foam. In this embodiment, the expandable material can be added as a coating layer that is present on at least the outer surface of the foam and may or may not penetrate the pores of the foam to coat the inner surface. Coating can be done, for example, by spray coating, dip coating, flow coating, roll coating, etc. The coating layer on at least the outer surface of the foam can have a thickness of 5 micrometers to 3 millimeters, or 25 to 250 micrometers. As mentioned above, it has surprisingly been found that the coating layer does not substantially adversely affect the desired properties of the foam, such as the compression force deflection or compression set of the foam.
[0046]
[0051] The expandable material can be present in the reactive composition including the polyurethane precursor composition, e.g., in the foam mixture 10, prior to forming the polyurethane foam. Conversely, the expandable material can be added as a layer onto the formed polyurethane foam. For example, the expandable material can be added after the heating zone by continuously feeding the expandable composition 54 onto the polyurethane foam. The expandable composition 54 can be spread into a layer of desired thickness by a doctor blade 56 or other suitable application device. Conversely, (not shown), the method can include traversing the polyurethane foam after the release liner is removed through a bath including the expandable composition 54 before being wrapped around the roll 40.
[0047]
[0052] After the polyurethane foam is formed into the desired shape of the battery pad, an expandable material can be added to the polyurethane foam. In this method, the expandable composition can be deposited on at least one surface of the polyurethane foam by at least one of spray coating, dip coating, painting, flow coating, etc. It should be noted that when the expandable composition is deposited by a liquid immersion method such as dip coating, an increased amount of the expandable composition can be present not only on the surface but also in some cases within the foam.
[0048]
[0053] The expandable battery pad can have a thickness of 0.1-26 mm, or 0.1-15 mm, or 0.3-10 mm, or 1-5 mm, or 5-6 mm. The polyurethane foam can have a thickness of 0.1-26 mm, or 0.1-15 mm, or 0.3-10 mm, or 1-5 mm, or 5-6 mm. The thickness can be in the z direction as shown in FIG.
[0049]
[0054] Expandable battery pads: 100-1,040kg / m 3 , or 100-500, or 300-400kg / m 3 The density may be determined in accordance with ASTM D3574-95, Test A.
[0050]
[0055] The expandable battery pad may have a compression force deflection at 25% deflection of 5 to 1,035 kilopascals (kPa), or 5 to 500 kPa, or 100 to 250 kPa, or 25 to 80 kPa. Note that the compression force deflection at 25% refers to the load required to physically compress the polyurethane foam by 25%. The expandable battery pad may have a compression force deflection at 75% deflection of 50 to 1,050 kPa, 100 to 500 kPa, or 200 to 300 kPa. Compressive force deflection as used herein may be determined according to ASTM D3574-17. The expandable battery pad may have a SAG factor of 3 or less, defined as the compression force deflection at 65% divided by the compression force deflection at 25%.
[0051]
[0056] The expandable battery pads may have a compression set at 50% deflection of 0-15% or 0-5%, as determined according to ASTM D3574-95, Test D at 23°C or 70°C.
[0052]
[0057] An expandable battery pad, particularly for use with lithium ion batteries, can include a polyurethane foam having a compression force deflection of 5 to 1,035 kPa at 25% deflection determined according to ASTM D3574-17; and an expandable material including an acid source, a carbon source, and a blowing agent; wherein the expandable battery pad has a UL-V0 rating at 1 mm. The battery pad can have a thickness of 1 to 5 mm. The compression force deflection can be 5 to 500 kPa, or 5 to 80 kPa, at 25% deflection. The polyurethane can have a compression force deflection of 100 to 500 kPa, or 200 to 300 kPa, at 75% deflection determined according to ASTM D3574-17. The polyurethane can have a compression set at 50% deflection of 0 to 15% or 0 to 5% as determined according to ASTM D3574-95, Test D at 23° C. or 70° C. The polyurethane may have a SAG factor of 3 or less, defined as the compression deflection at 65% divided by the compression deflection at 25%. The acid source may include at least one of organic or inorganic phosphorus or sulfate. The organic or inorganic phosphorus compound may include at least one of tris(2,3-dibromopropyl)phosphate, tris(2-chloroethyl)phosphate, tris(2,3-dichloropropyl)phosphate, tris(1-chloro-3-bromoisopropyl)phosphate, bis(1-chloro-3-bromoisopropyl)-1-chloro-3-bromoisopropylphosphonate, polyaminotriazine phosphate, melamine phosphate, or guanylurea phosphate; an organic phosphate ester; or a phosphorus-containing inorganic compound. The carbon source may include at least one of dextrin, phenol-formaldehyde resin, pentaerythritol, clay, or polymer. The carbon source may include polyurethane foam. The blowing agent may include at least one of dicyandiamide, azodicarbonamide, melamine, guanidine, glycine, urea, or a halogenated organic material. The blowing agent may decompose at a temperature of 120° C. or higher, or between 130° C. and 200° C. The intumescent material may further include at least one of a synergist or a binder.The expandable material can be present on at least one surface of the polyurethane foam. The expandable material can be dispersed throughout the polyurethane foam. The expandable material can be disposed on all surfaces of the expandable battery pad.
[0053]
[0058] The battery assembly may include at least two battery cells; and an expandable battery pad disposed between the at least two battery cells. The battery may be a lithium ion battery.
[0054]
[0059] The expandable battery pad can be formed by coating a foam composition including a reactive mixture onto a release liner and curing the reactive mixture to form a polyurethane foam. The foam composition can include an expandable material, and / or the method can further include depositing the expandable material onto at least one surface of the polyurethane foam to form the expandable battery pad. Coating the foam composition can include depositing the foam composition onto a release liner at a deposition location; curing the reactive mixture includes moving the foam composition and the release liner through a heating zone to cure the reactive mixture, thereby forming a polyurethane foam. Depositing the expandable material can include moving the polyurethane foam from the heating zone to an expandable material deposition zone and depositing the expandable material onto the polyurethane foam. Depositing the expandable material can include moving the polyurethane foam from the heating zone to an expandable material soaking zone and providing the expandable material onto the polyurethane foam. The foam composition can include an expandable material.
[0055]
[0060] The expandable battery pad can be formed by depositing an expandable material coating onto a polyurethane foam, which can include dip coating, flow coating, or spray coating.
[0056]
[0061] The following examples are provided to illustrate the present disclosure. The examples are merely illustrative and are not intended to limit devices made according to the present disclosure to the materials, conditions, or process parameters described herein.
[0057] Working Example Example 1
[0062] Seven pieces of PORON brand polyurethane foam were cut into strips having a thickness of 3 mm. The intumescent paint was spread over the broad surface of three pieces of polyurethane foam and three pieces of polyurethane foam were dip coated in the intumescent paint. The seventh piece of polyurethane foam did not contain the intumescent paint.
[0058]
[0063] The samples were then tested at 1 millimeter thickness according to the Underwriters' Laboratory (UL)-94 flammability test. Figure 7 shows the samples after flammability testing, where the three polyurethane foams on the left were painted and the three polyurethane foams on the right were dip coated. The dip coated polyurethane foams achieved a UL-94 V0 rating and show a relatively small amount of char at the top of the foam. The painted polyurethane foams achieved a UL-94 V1 rating, where Figure 7 shows some charring, especially towards the top of the foam. The increased charring compared to the dip coated foams is due to the edges of the foam not being coated with paint. The seventh polyurethane foam, which was not coated with intumescent paint, burned completely.
[0059]
[0064] Set forth below are various non-limiting aspects of the present disclosure.
[0060]
[0065] Aspect 1: An expandable battery pad for a lithium ion battery comprising: a polyurethane foam having a compressive force deflection at 25% deflection of 5 to 1,035 kilopascals determined according to ASTM D3574-17; and an expandable material comprising an acid source, a carbon source, and a blowing agent; wherein the expandable battery pad has a UL-V0 rating at a thickness of 1 millimeter.
[0061]
[0066] Aspect 2: The expandable battery pad of Aspect 1, wherein the expandable battery pad has a thickness of 1 to 5 mm.
[0062]
[0067] Aspect 3: The expandable battery pad of any one or more of the preceding aspects, wherein the polyurethane foam has at least one of: a compression force deflection at 25% deflection determined in accordance with ASTM D3574-17 of 5-500 kPa or 5-80 kPa, respectively; a compression force deflection at 75% deflection determined in accordance with ASTM D3574-17 of 100-500 kPa or 200-300 kPa, respectively; a compression set at 50% deflection of 0-15% or 0-5%, determined in accordance with ASTM D3574-95, Test D at 23° C. or 70° C.; or a SAG factor of 3 or less, defined as the compression force deflection at 65% divided by the compression force deflection at 25%.
[0063]
[0068] Embodiment 4: The expandable battery pad of any one or more of the preceding embodiments, wherein the acid source comprises at least one of an organic or inorganic phosphorus or sulfate (e.g., ammonium sulfate); and the organic or inorganic phosphorus compound can comprise at least one of tris(2,3-dibromopropyl)phosphate, tris(2-chloroethyl)phosphate, tris(2,3-dichloropropyl)phosphate, tris(1-chloro-3-bromoisopropyl)phosphate, bis(1-chloro-3-bromoisopropyl)-1-chloro-3-bromoisopropylphosphonate, polyaminotriazine phosphate, melamine phosphate, or guanylurea phosphate; an organic phosphate ester; or a phosphorus-containing inorganic compound.
[0064]
[0069]
[0023] Embodiment 5: The expandable battery pad of any one or more of the preceding embodiments, wherein the carbon source includes at least one of dextrin, phenol-formaldehyde resin, pentaerythritol (e.g., a dimer or trimer thereof), clay, or a polymer (e.g., polyamide 6 or polyurethane foam).
[0065]
[0070]
[0023] Aspect 6: The expandable battery pad of any one or more of the preceding aspects, wherein the blowing agent includes at least one of dicyandiamide, azodicarbonamide, melamine, guanidine, glycine, urea (e.g., urea-formaldehyde resin or methylolated guanylurea phosphate), or a halogenated organic material (e.g., chlorinated paraffin).
[0066]
[0071] Aspect 7: The expandable battery pad of any one or more of the preceding aspects, wherein the foaming agent decomposes at a temperature above 120°C, or between 130 and 200°C.
[0067]
[0072]
[0046] Embodiment 8: The expandable battery pad of any one or more of the preceding embodiments, wherein the expandable material further comprises at least one of a synergist or a binder.
[0068]
[0073]
[0046] Embodiment 9: The expandable battery pad of any one or more of the preceding embodiments, wherein the expandable material is present on at least one surface of the polyurethane foam.
[0069]
[0074]
[0036] Embodiment 10: The expandable battery pad of any one or more of the preceding embodiments, wherein the expandable material is dispersed in the polyurethane foam.
[0070]
[0075]
[0041] Embodiment 11: The expandable battery pad of any one or more of the preceding embodiments, wherein the expandable material is disposed on all surfaces of the expandable battery pad.
[0071]
[0076] Example 12: A battery comprising: at least two battery cells; and an expandable battery pad of any one or more of the preceding examples disposed between the at least two battery cells.
[0072]
[0077] Example 13: The battery of example 12, wherein the battery is a lithium ion battery.
[0073]
[0078] Aspect 14: A method of making an expandable battery pad (e.g., of any one or more of Aspects 1-11), comprising: coating a foam composition comprising a reactive mixture onto a release liner; and curing the reactive mixture to form the polyurethane foam; wherein the foam composition comprises the expandable material or the method further comprises depositing the expandable material on at least one surface of the polyurethane foam to form the expandable battery pad.
[0074]
[0079] Aspect 15: The method of aspect 14, wherein the step of coating the foam composition comprises depositing the foam composition at a deposition location on the release liner; and the step of curing the reactive mixture comprises moving the foam composition and the release liner through a heating zone to cure the reactive mixture and form the polyurethane foam.
[0075]
[0080] Aspect 16: The method of aspect 15, wherein the step of depositing the expandable material comprises the steps of moving the polyurethane foam from the heating zone to an expandable material deposition zone and depositing the expandable material onto the polyurethane foam.
[0076]
[0081] Aspect 17: The method of aspect 15, wherein the step of depositing the expandable material includes the step of moving the polyurethane foam from the heating zone to an expandable material immersion zone to provide the expandable material on the polyurethane foam.
[0077]
[0082]
[0041] Aspect 18: The method of any one or more of aspects 14-17, wherein the foam composition comprises the expandable material.
[0078]
[0083] Aspect 19: A method of making an expandable battery pad (e.g., of any one or more of Aspects 1-11), comprising depositing the expandable material onto the polyurethane foam.
[0079]
[0084] Aspect 20: The method of aspect 19, wherein the depositing step comprises dip coating, flow coating, or spray coating.
[0080]
[0085] Example 21: A battery assembly comprising at least two battery cells and an expandable battery pad (e.g., of any of Examples 1-11) disposed between the at least two battery cells or along a surface adjacent to the battery assembly; the expandable battery pad comprising polyurethane foam and a layer of expandable material on the polyurethane foam.
[0081]
[0086] Aspect 22: The battery assembly of aspect 21, wherein the expandable material layer is disposed on all outer surfaces of the polyurethane foam.
[0082]
[0087] Aspect 23: The battery assembly of any of Aspects 21-22, wherein the expandable material layer is present on at least one outer surface of the polyurethane foam.
[0083]
[0088]
[0041] Aspect 24: The battery assembly of any of Aspects 21-23, wherein the polyurethane foam has a thickness of 1 to 5 millimeters.
[0084]
[0089] Aspect 25: The battery assembly of any of aspects 21 to 24, wherein the polyurethane foam has a thickness of 1 to 5 millimeters; and the expandable material layer has a thickness of 25 to 250 micrometers.
[0085]
[0090] Aspect 26: The battery assembly of any of aspects 21-25, wherein the thickness of the expandable material layer is less than the thickness of the polyurethane layer; and the expandable material layer has a thickness of 5 micrometers relative to 3 millimeters.
[0086]
[0091] Example 27: The battery assembly of any of Examples 21-26, wherein the expandable battery pad and at least one of the battery cells each have the same peripheral shape.
[0087]
[0092] Embodiment 28: The battery assembly of any of embodiments 21-27, wherein the expandable battery pad and the at least two battery cells each have the same peripheral shape and peripheral size.
[0088]
[0093] Example 29: The battery assembly of any of Examples 21-28, wherein the expandable battery pad and at least one of the battery cells have different perimeter shapes along at least a portion of the perimeter of the expandable battery pad.
[0089]
[0094] Aspect 30: The battery assembly of any of aspects 21-29, wherein the battery assembly includes a stack of 2-100 or 10-50 battery cells, and the expandable battery pad is disposed between each battery cell in the stack.
[0090]
[0095] Embodiment 31: A battery comprising the battery assembly of any of embodiments 21-30.
[0091]
[0096] Example 32: The battery of example 31, wherein the battery assembly is disposed within a housing; a foam layer is disposed on a first side of the battery assembly within the housing, and a thermal management assembly is disposed on a second side of the battery assembly; and the thermal management assembly includes a thermal interface layer and a cooling plate.
[0092]
[0097] Example 33: The battery of example 31 or 32, wherein the battery is a lithium ion battery.
[0093]
[0098] The compositions, methods and articles can alternatively comprise, consist of, or consist essentially of any suitable material, step or ingredient disclosed herein. The compositions, methods and articles can additionally, or alternatively, be formulated to be devoid of, or substantially free of, any material (or species), step or ingredient that is not necessary to achieve the function or purpose of the compositions, methods and articles.
[0094]
[0099] The terms "a" and "an" do not denote a limitation of quantity, but rather denote the presence of at least one of the referenced items. The term "or" means "and / or" unless the context clearly indicates otherwise. References throughout this specification to "one aspect," "one embodiment," "another embodiment," "some embodiments," and the like, mean that a particular element (e.g., a feature, structure, step, or characteristic) described in connection with this embodiment is included in at least one embodiment described herein and may or may not be present in other embodiments. Furthermore, it should be understood that the described elements can be combined in any suitable manner in the various embodiments.
[0095]
[0100] When an element such as a layer, film, region, or substrate is referred to as being on another element, it can be directly on the other element, or intervening elements may be present as well. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements present.
[0096]
[0101] Unless otherwise stated herein, all test standards are the latest standards in effect as of the filing date of this application or, if priority is claimed, the filing date of the earliest priority application in which the test standard appears.
[0097]
[0102] The endpoints of all ranges directed to the same component or property are inclusive, independently combinable, and include all intermediate points and ranges. For example, a range of "up to 25% by weight, or up to 5-20% by weight" includes the endpoints and all intermediate values of the range "5-25% by weight," such as 10-23% by weight. As used herein, the terms "first," "second," and the like, "primary," "secondary," and the like, do not denote any order, quantity, or importance, but rather are used to distinguish one element from another. The term "combination including at least one of the foregoing" or "at least one of" means that the list includes each element individually, as well as combinations of two or more elements of the list, and combinations of at least one element of the list with similar elements not named. The term "combination" also includes blends, mixtures, alloys, reaction products, and the like.
[0098]
[0103] Unless otherwise defined, technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs.
[0099]
[0104] Compounds are described using standard nomenclature. For example, any position not substituted by any shown group is understood to have its valence filled by the shown bond or hydrogen atom. A dash ("-") that is not between two letters or symbols is used to indicate the point of attachment of a substituent. For example, -CHO is attached through the carbon of a carbonyl group.
[0100]
[0105] All cited patents, patent applications, and other references are incorporated herein by reference in their entirety. However, if a term in this application contradicts or conflicts with a term in an incorporated reference, the term from this application takes precedence over the conflicting term from the incorporated reference.
[0101]
[0106] While particular embodiments have been described, alternatives, modifications, variations, improvements, and substantial equivalents that are not presently foreseen or may not be foreseen may occur to applicant or others skilled in the art, and it is accordingly intended that the appended claims shall embrace all such alternatives, modifications, variations, improvements, and substantial equivalents as filed and as amended.
Claims
1. a polyurethane foam having a compression force deflection at 25% deflection determined according to ASTM D3574-17 of 5 to 1,035 kilopascals; a coating layer having a thickness of 25 to 250 micrometers on at least an outer surface of the polyurethane foam, the coating layer comprising an expandable material including an acid source, a carbon source, and a blowing agent; 1. An expanding battery pad for a lithium ion battery comprising: the expandable battery pad has a UL-V0 rating at a thickness of 1 millimeter; the acid source comprises at least one of an organic or inorganic phosphorus compound or a sulfate salt (e.g., ammonium sulfate); the organic or inorganic phosphorus compound may comprise at least one of tris(2,3-dibromopropyl)phosphate, tris(2-chloroethyl)phosphate, tris(2,3-dichloropropyl)phosphate, tris(1-chloro-3-bromoisopropyl)phosphate, bis(1-chloro-3-bromoisopropyl)-1-chloro-3-bromoisopropylphosphonate, polyaminotriazine phosphate, melamine phosphate, or guanylurea phosphate; an organic phosphate ester; or a phosphorus-containing inorganic compound; the phosphorus-containing inorganic compound is phosphoric acid, phosphorous acid, a phosphite, a urea phosphate, or an ammonium phosphate; The expandable battery pad, wherein the carbon source comprises at least one of dextrin, phenol-formaldehyde resin, pentaerythritol (eg, a dimer or trimer thereof), or a polymer (eg, polyamide 6 or polyurethane foam).
2. The expandable battery pad of claim 1 , wherein the expandable battery pad has a thickness of 1 to 5 millimeters.
3. The polyurethane foam is Compressive deflection at 25% deflection determined according to ASTM D3574-17 of 5 to 500 kPa or 5 to 80 kPa, respectively; Compressive deflection of 100-500 kPa or 200-300 kPa, respectively, at 75% deflection determined according to ASTM D3574-17; Compression set at 50% deflection of 0-15% or 0-5% determined according to ASTM D3574-95, Test D at 23°C or 70°C; or A SAG factor of 3 or less, defined as the compression deflection at 65% divided by the compression deflection at 25%; 3. The expandable battery pad of claim 1 or 2, comprising at least one of:
4. 4. The expandable battery pad of claim 1, wherein the foaming agent comprises at least one of dicyandiamide, azodicarbonamide, melamine, guanidine, glycine, urea, urea-formaldehyde resin, methylolated guanylurea phosphate, or a halogenated organic material (e.g., chlorinated paraffin).
5. 5. The expandable battery pad of any one of claims 1 to 4, wherein the foaming agent decomposes at a temperature above 120°C or between 130 and 200°C.
6. 6. The expandable battery pad of claim 1, wherein the expandable material further comprises at least one of a synergist or a binder.
7. 7. The expandable battery pad of claim 1, wherein the expandable material is disposed on all surfaces of the expandable battery pad.
8. at least two battery cells; An expandable battery pad according to any one of claims 1 to 7, disposed between the at least two battery cells; A battery comprising:
9. 9. The battery of claim 8, wherein the battery is a lithium ion battery.
10. coating a foam composition comprising the reactive mixture onto a release liner; curing the reactive mixture to form the polyurethane foam; Including, 8. The method of making an expandable battery pad according to any one of claims 1 to 7, wherein the foam composition comprises the expandable material or the method further comprises depositing the expandable material on at least one surface of the polyurethane foam to form the expandable battery pad.
11. 11. The method of claim 10, wherein coating the foam composition comprises depositing the foam composition at a deposition location on the release liner; and curing the reactive mixture comprises moving the foam composition and the release liner through a heating zone to cure the reactive mixture and form the polyurethane foam.
12. 12. The method of claim 11, wherein depositing the expandable material comprises moving the polyurethane foam from the heating zone to an expandable material deposition zone and depositing the expandable material onto the polyurethane foam.
13. 12. The method of claim 11, wherein depositing the intumescent material comprises moving the polyurethane foam from the heating zone to an intumescent material soaking zone to provide the intumescent material on the polyurethane foam.
14. The method of any one of claims 10 to 13, wherein the foam composition comprises the expandable material.
15. A method of making an expandable battery pad according to any one of claims 1 to 7, comprising depositing the expandable material onto the polyurethane foam.
16. The method of claim 15 , wherein the depositing step comprises dip coating, flow coating, or spray coating.
17. 1. A battery assembly comprising: At least two battery cells; an expandable battery pad according to any one of claims 1 to 7 disposed between the at least two battery cells or along a surface adjacent to the battery assembly; With The battery assembly, wherein the expandable battery pad comprises a polyurethane foam and an expandable material layer on the polyurethane foam.
18. 20. The battery assembly of claim 17, wherein the expandable material layer is disposed on all outer surfaces of the polyurethane foam.
19. 19. The battery assembly of claim 17 or 18, wherein the polyurethane foam has a thickness of 1 to 5 millimeters.
20. The battery assembly of any one of claims 17 to 19, wherein the polyurethane foam has a thickness of 1 to 5 millimeters.
21. The battery assembly of any one of claims 17 to 20, wherein the thickness of the expandable material layer is less than the thickness of the polyurethane foam.
22. 22. The battery assembly of claim 17, wherein the expandable battery pad and at least one of the battery cells each have the same peripheral shape.
23. 23. The battery assembly of any one of claims 17 to 22, wherein the expandable battery pad and the at least two battery cells each have the same peripheral shape and peripheral size.
24. 24. The battery assembly of any one of claims 17 to 23, wherein the expandable battery pad and at least one of the battery cells have different perimeter geometries along at least a portion of a perimeter of the expandable battery pad.
25. 25. The battery assembly of any one of claims 17 to 24, wherein the battery assembly includes a stack of 2-100 or 10-50 battery cells, and the expandable battery pad is disposed between each battery cell in the stack.
26. A battery comprising the battery assembly of any one of claims 17 to 25.
27. the battery assembly is disposed within a housing; a foam layer is disposed within the housing on a first side of the battery assembly and a thermal management assembly is disposed on a second side of the battery assembly; 27. The battery of claim 26, wherein the thermal management assembly includes a thermal interface layer and a cold plate.
28. 28. The battery of claim 26 or 27, wherein the battery is a lithium ion battery.
Citation Information
Patent Citations
Battery housing assembly
JP1993190162A
Foam fire-resistant laminated body and its formation
JP2000230287A
Use of expandable flameproofing coating material for fireproof finish processing of article and fireproof finish processed article
JP2004027219A
Low density polyurethane foam, its production method, and article including it
JP2007044972A
Method for producing foam urethane sheet
JP2013256558A